2020
DOI: 10.1177/0033354920966024
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic: An Opportunity to Transform Higher Education in Public Health

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has revealed deficiencies in our public health infrastructure and led to calls for long-overdue investment, an improved focus on equity, and new approaches to crisis readiness and response. Higher education in public health faces a similar moment of reckoning. The immediacy of the pandemic forced schools and programs of public health to shift to remote learning and to support response efforts. The pandemic provides an opportunity to consider fundamental changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
(2 reference statements)
0
12
0
Order By: Relevance
“…A rapid change in the education system, from the face-to-face classroom to web-based distance learning, was challenging for most teachers and their students [ 2 , 3 , 4 , 5 , 6 ]. The dynamic changes and transformation process required adaptation and resilience skills which relied mainly on the acquisition of new teaching practices and strategies as well as on learning new technological tools and applications compensating for previous face-to-face activities [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, adjustment to a unique situation was experienced as highly stressful [ 13 , 14 ], significantly contributing to higher rates of anxiety and depression and lower quality of work and life [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rapid change in the education system, from the face-to-face classroom to web-based distance learning, was challenging for most teachers and their students [ 2 , 3 , 4 , 5 , 6 ]. The dynamic changes and transformation process required adaptation and resilience skills which relied mainly on the acquisition of new teaching practices and strategies as well as on learning new technological tools and applications compensating for previous face-to-face activities [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, adjustment to a unique situation was experienced as highly stressful [ 13 , 14 ], significantly contributing to higher rates of anxiety and depression and lower quality of work and life [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic demonstrated that even the states with relatively well-developed public health infrastructures faced problems during the COVID-19 outbreak. While the pandemic has revealed deficiencies in public health infrastructure and education of the public health workforce, it also created an opportunity to reassess and make substantial changes in the educational systems for public health for the long-term benefit ( 2 , 3 ). From this perspective, COVID-19 is the biggest concern and momentum for reflection for the world, including for the Former Soviet Union (FSU) countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pandemic has shown that there is a need to re-evaluate educational programs in many developing countries; early career researchers, policymakers in public health are all looking for ways to build public health workforce in the world of research, and this would require re-considering the skill-mix and competencies, creating trans-national inter-university teaching and learning environments ( 9 )to better equip the students with the knowledge and skills enabling them to tackle future challenges and contribute to the global scientific conversation in the field of public health ( 10 ). Thus, pandemic provides an opportunity to consider fundamental changes and improve the approaches to, effectiveness in, and impact on public health education and the public health system to better cope with crises in the future ( 2 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has revealed opportunities for public health and primary care infrastructure to better target the social and structural determinants of health, and to promote health equity [ 1 ]. Disparities in incidence and mortality of COVID-19 have been documented by race/ethnicity [ 2 ] and socioeconomic status [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%